## Inequalities Quiz - 20

#### Quiz-summary

0 of 10 questions completed

Questions:

- 1
- 2
- 3
- 4
- 5
- 6
- 7
- 8
- 9
- 10

#### Information

Hello Aspirants,

Study Virus is providing most important Quizzes on **“Inequalities”** which can be very helpful for Bank Jobs Aspirants.These questions are very important for all banking exams like SBI Clerk,SBI PO,IBPS Clerk,IBPS PO,NIACL,RRB,etc.We have also included many questions which were asked in previous years.

You have already completed the quiz before. Hence you can not start it again.

Quiz is loading...

You must sign in or sign up to start the quiz.

You have to finish following quiz, to start this quiz:

#### Results

0 of 10 questions answered correctly

Your time:

Time has elapsed

You have reached 0 of 0 points, (0)

#### Categories

- Not categorized 0%

⇒ Please share your marks in comment section.

⇒Ask your doubts too in comment section, we will try our best to clear all your doubts.

**Keep Working Hard and Never Give Up**

- 1
- 2
- 3
- 4
- 5
- 6
- 7
- 8
- 9
- 10

- Answered
- Review

- Question 1 of 10
##### 1. Question

Directions:(1-5)

**In the following question assuming the given statements to be true, find which of the conclusion among given conclusions is /are definitely true and then give your answers accordingly.****Statement:**E = O

**;**E < J < I ≤ B; C > L > K > O; J = L; C < M > B

**Conclusion:**I. C > I

II. I = CCorrectGiven statement: E = O; E < J < I ≤ B; C > L > K > O; J = L; C < M > B

On combining: E = O < K < J = L < I ≤ B < M; C > L; C < M

I. C > I → False (L < I; L < C, → There is no relation between C and I)

II. I = C → False (L < I; L < C, → There is no relation between C and I)

Hence, neither I nor II follow.IncorrectGiven statement: E = O; E < J < I ≤ B; C > L > K > O; J = L; C < M > B

On combining: E = O < K < J = L < I ≤ B < M; C > L; C < M

I. C > I → False (L < I; L < C, → There is no relation between C and I)

II. I = C → False (L < I; L < C, → There is no relation between C and I)

Hence, neither I nor II follow. - Question 2 of 10
##### 2. Question

**Statements:**P < L < A = N > E > D; Q > N < O

**Conclusions:**I) L < E

II) P < QCorrectGiven statements: P < L < A = N > E > D; Q > N < O

On combining: P < L < A = N < Q; O > N > E > D

I) L < E → False (as, L < A = N > E → No relation found between L and E)

II) P < Q → True (as, P < L < A = N < Q → P < Q)

Therefore, only Conclusion II is true.IncorrectGiven statements: P < L < A = N > E > D; Q > N < O

On combining: P < L < A = N < Q; O > N > E > D

I) L < E → False (as, L < A = N > E → No relation found between L and E)

II) P < Q → True (as, P < L < A = N < Q → P < Q)

Therefore, only Conclusion II is true. - Question 3 of 10
##### 3. Question

**Statements:**T < G < Q; M = W > Y; Q = L ≥ K < Y

**Conclusions:**I)T < L

II) K < MCorrectFor conclusion I: T < L

Combining statement I and III we get,

T < G < Q = L

Here, the common sign between T and L is ‘<’ and the given conclusion is T < L, hence conclusion I follows.

For conclusion II: K < M

Combining statements II and III we get,

K < Y < W = M

Here, the common sign between K and M is ‘<‘ and the given conclusion is K < M, hence conclusion II follows

Hence, the correct answer would be both conclusions I and II follow.IncorrectFor conclusion I: T < L

Combining statement I and III we get,

T < G < Q = L

Here, the common sign between T and L is ‘<’ and the given conclusion is T < L, hence conclusion I follows.

For conclusion II: K < M

Combining statements II and III we get,

K < Y < W = M

Here, the common sign between K and M is ‘<‘ and the given conclusion is K < M, hence conclusion II follows

Hence, the correct answer would be both conclusions I and II follow. - Question 4 of 10
##### 4. Question

**Statements:**S > J = B < E; M > D = U; E > W > U

**Conclusions:**I) E > D

II) B > MCorrect**For conclusion I**: E > D

From statements II and III: E > W > U = D, we get common sign of ‘>’ between E and D, hence, E > D follows.

**For Conclusion II**: B > M

From statements I, II and III: M > D = U < E > B, we get opposite signs between B and M, hence, B > M does not follow.

Hence, the correct answer would be only conclusion I follow.Incorrect**For conclusion I**: E > D

From statements II and III: E > W > U = D, we get common sign of ‘>’ between E and D, hence, E > D follows.

**For Conclusion II**: B > M

From statements I, II and III: M > D = U < E > B, we get opposite signs between B and M, hence, B > M does not follow.

Hence, the correct answer would be only conclusion I follow. - Question 5 of 10
##### 5. Question

**Statements:**A = X ≥ L; E ≤ J ≤ F; L ≥ Z = E

**Conclusions:**

I) A < Z

II) Z > FCorrect**For conclusion I**: A < Z

Combining statements I and III, we get:

A = X ≥ L ≥ Z

Here, the common sign between A and Z is ‘≥’ and the given conclusion is A < Z, hence, A < Z does not follows.

**For conclusion II**: Z > F

Combining statements II and III, we get:

Z = E ≤ J ≤ F

Here, common sign between Z and F ‘≤’ and the given conclusion is Z > F, hence, Z > F does not follows.

Hence, the correct answer would be neither conclusion follows.Incorrect**For conclusion I**: A < Z

Combining statements I and III, we get:

A = X ≥ L ≥ Z

Here, the common sign between A and Z is ‘≥’ and the given conclusion is A < Z, hence, A < Z does not follows.

**For conclusion II**: Z > F

Combining statements II and III, we get:

Z = E ≤ J ≤ F

Here, common sign between Z and F ‘≤’ and the given conclusion is Z > F, hence, Z > F does not follows.

Hence, the correct answer would be neither conclusion follows. - Question 6 of 10
##### 6. Question

Directions:(6-10)

**In these questions relationship between different elements is shown in the statements. Study the conclusions based on the given statement and select the appropriate answer.**

**Statements:**

A < D = M ≥ R; S ≥ M ≥ N

**Conclusions:**

I. R < S

II. R = SCorrect**S ≥ M ≥ R**Conclusions:

I. R < S ( Not True )

II. R = S (Not True)Incorrect**S ≥ M ≥ R**Conclusions:

I. R < S ( Not True )

II. R = S (Not True) - Question 7 of 10
##### 7. Question

**Statements:**

E > Z = U ≥ T; Y > U ≥ X

**Conclusions:**

I. E > Y

II. E > XCorrectConclusions:

I. E > Y (Not True) (E > U <Y)

II. E > X (True) (E > U ≥ X)IncorrectConclusions:

I. E > Y (Not True) (E > U <Y)

II. E > X (True) (E > U ≥ X) - Question 8 of 10
##### 8. Question

**Statements:**

A ≥ B ≤ C = T, A < L ≥ V

**Conclusions:**

I. V ≤ C

II. C > VCorrectV ≤ L >A ≥ B ≤ C

Conclusions:

I. V ≤ C ( Not True )

II. C > V (Not True)IncorrectV ≤ L >A ≥ B ≤ C

Conclusions:

I. V ≤ C ( Not True )

II. C > V (Not True) - Question 9 of 10
##### 9. Question

**Statements:**

D < E ≤ C; A > D; B ≥ C

**Conclusions:**

I. B > D

II. A ≥ CCorrectConclusions:

A >D < E ≤ C≤ B

I. B > D (True)

II. A ≥ C (Not True)IncorrectConclusions:

A >D < E ≤ C≤ B

I. B > D (True)

II. A ≥ C (Not True) - Question 10 of 10
##### 10. Question

**Statements:**

D > E ≥ C; A > D; B ≥ C

**Conclusions:**

I. A > C

II. E < ACorrectA >D > E ≥ C

Conclusions:

I. A > C ( True )

II. E < A ( True )IncorrectA >D > E ≥ C

Conclusions:

I. A > C ( True )

II. E < A ( True )